Strategi Pembentukan Karakter Santri Berbasis Profil Pelajar Pancasila di Ponpes At-Taujieh Al-Islamy 2 Leler Banyumas - Herman Wicaksono; M. Alifian Ferdi Ikhsan (Kuttab: Jurnal Ilmu Pendidikan Islam, 2025)
This study aims to describe the strategies of At-Taujieh Al-Islamy Islamic Boarding School 2 in Leler, Banyumas, in developing students’ character based on the Pancasila Student Profile. Using a qualitative approach, data were collected through participatory observation, in-depth interviews, and documentation, then analyzed descriptively with triangulation techniques. The findings reveal four main character-building strategies: (1) role modeling, (2) habituation, (3) guidance, and (4) the use of rewards and punishments. These strategies effectively foster students’ faith, piety, noble character, global outlook, independence, creativity, and critical thinking—reflected through disciplined worship, international engagement, self-reliance, artistic expression, and regular bahtsul masail discussions.